The Optimalization of Coal Mining Supervision for the Environmental Law Enforcement on Post-Mining Activities - Putri Swastika Hidayah (Universitas Slamet Riyadi, 2020)
Many coal mining companies are reluctant to carry out reclamation and post-mining, of course, resulting in environmental, ecological and community losses. Therefore this article tries to parse and explain the role and function of supervision as an effort to enforce administrative law related to the obligation to conduct reclamation by coal mining companies in order to preserve the environment and provide public justice. In addition, it also describes the construction related to withdrawing good post-mining reclamation funds in an effort to overcome the bad faith of the mining company. This research is a type of normative legal research. In this research, it is known that this is a result of the lack of intensity of supervision carried out by the government both before the Mining Business License (IUP) is issued or after the IUP is issued. First, in the case of supervision prior to the issuance of IUPs, it is known that many of the management of IUPs are issued without attaching reclamation and post-mining plans which are actually mandated by Article 99 (1) of Law 02/2009 which should be a reference for supervision of companies in conducting post-mining reclamation. Second, in terms of supervision after the issuance of IUP, it is known that the regulation on supervision, work mechanism, distribution of supervisors in mining areas, action models, is a problem that has never been well formulated to date. Then related to the large number of mining companies that have not provided reclamation and post-mining guarantee funds, it is known as a result of the regulation regarding withdrawal of post-mining Reclamation funds not clearly regulated in mining law in Indonesia.